A clinical decisions unit improves emergency general surgery care delivery. Issue 4 (5th October 2015) - Johnstone, Chris; Harwood, Rachel; Gilliam, Andrew; Mitchell, Andrew
Abstract : Purpose: – Early access to senior decision makers and investigations has improved outcomes for many conditions. A surgical clinical decisions unit (CDU) was created to allow rapid assessment and investigation by on-call senior surgical team members to facilitate decision making and, if appropriate, discharge within a set time frame (less than four hours). The purpose of this paper is to compare outcomes for unscheduled general surgery admissions to the hospital before and after commissioning this unit. Design/methodology/approach: – Prospectively collected hospital episode statistics data were compared for all general surgical admissions for one year prior to (July 2010-June 2011) and two years after (July 2011-June 2013) the introduction of the CDU. Statistical analysis using the Mann Whitney U -test was performed. Findings: – More patients were discharged within 24 hours (12 per cent vs 20 per cent, p < 0.001) and total hospital stay decreased (4.6 days vs 3.2 days, p < 0.001) following introduction of CDU. Admission via A & E (273 vs 212, p < 0.01) was also decreased. Overall there was a 25.3 per cent reduction in emergency surgical admissions. No difference was noted in 30-day readmission rates (47 vs 49, p =0.29). Originality/value: – The introduction of a CDU in has increased early discharge rates and facilitated safe early discharge, reducing overall hospital stay for unscheduled general surgical admissions. This has decreased fixed bed costs and improved patient flow by decreasing surgical care episodes routed through the emergency department (ED). In all, 30-day readmission rates have not been influenced by shorter hospital stay. Service redesign involving early senior decision making and patient investigation increases efficiency and patient satisfaction within unscheduled general surgical care. Not original but significant in that the model has not been widely implemented and this is a useful addition to the literature.